PENGARUH DZIKIR TERHADAP NEUROPLASTISITAS OTAK: PERSPEKTIF AL-QUR’AN DALAM MENINGKATKAN KESEHATAN MENTAL - Rifqatul Husna; Arina Isa Salsabila; Salih Abdulrahman Alsounusi (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
In this modern era, mental health is an important aspect of human life that is often overlooked. The practice of dhikr, as a form of Islamic meditation, has been recognized in the Islamic tradition as a way to get closer to Allah and calm the soul. This study aims to identify the effect of dhikr on brain neuroplasticity and its implications for mental health. Using the thematic tafsir method, this study collects and analyzes Qur'anic verses related to dhikr and mental health, and examines books of tafsir as primary data sources, while secondary data are taken from books and scientific journal articles. The results show that the practice of dhikr can result in the formation of new neural pathways related to concentration, emotional control, and improved cognitive abilities. Regular dhikr activities are proven to strengthen the brain's synaptic connections and improve the optimization of brain function through engaged focus. These findings indicate a convergence between spiritual practices and scientific findings, making dhikr an effective way to improve mental health and overall quality of life